Fiscal Stimulus and Credibility in Emerging Countries - Kandil, Magda (IMF Working Papers; Working Paper ;, 2010)
Across a sample of thirty four emerging countries, the evidence shows the frequent existence of a pro-cyclical fiscal impulse. However, the scope for countercyclical policy increases with the availability of international reserves as it enhances credibility and mitigates concerns about the effect of expansionary fiscal policy on the cost of borrowing and debt service. The paper also examines the effectiveness of the fiscal policy in emerging countries in the short- and long-run and its underlying conditions, which does not appear to be uniform. In some cases, contractionary fiscal policy could stimulate growth in the short-run, if fiscal tightness lowers the cost of borrowing and debt service, and mitigates concerns about debt sustainability. However, an increase in international reserves is evident to mitigate these concerns. On the other hand, high inflation increases concerns about the impact of fiscal spending on inflationary expectations and the cost of borrowing, countering the effectiveness of the fiscal stimulus on output growth in the short-run. Where the debt burden is high, fiscal expansion has a longlasting negative effect on real growth.